2017
DOI: 10.1016/j.foodres.2017.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Physiological comparability of the harmonized INFOGEST in vitro digestion method to in vivo pig digestion

Abstract: Recently, a static in vitro digestion (IVD) protocol was published by Minekus and coworkers (Minekus et al., 2014) within the COST INFOGEST network. The protocol, concentrating on physiological enzyme activities had the main goal to improve the comparability of experimental data between labs. The protocol was validated in several inter-laboratory studies using skim milk powder (SMP) and indeed demonstrated improved harmonization compared with previous experiments with individual IVD protocols (Egger et al., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 24 publications
6
62
0
Order By: Relevance
“…We worked with complex mixtures of dietary components that underwent a transformation during the digestion process. We simulated the in vivo digestion process with the INFOGEST harmonized protocol [32], which is very close to in vivo pig protein hydrolysis, as demonstrated by Egger et al [46]. It has been shown that protein hydrolysates have different effects on the enteroendocrine system, mainly due to the presence of specific peptides [47].…”
Section: Discussionmentioning
confidence: 99%
“…We worked with complex mixtures of dietary components that underwent a transformation during the digestion process. We simulated the in vivo digestion process with the INFOGEST harmonized protocol [32], which is very close to in vivo pig protein hydrolysis, as demonstrated by Egger et al [46]. It has been shown that protein hydrolysates have different effects on the enteroendocrine system, mainly due to the presence of specific peptides [47].…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggested that despite data were inconclusive and more studies are still needed, there is some evidence indicating that differences in i) kinetics of protein hydrolysis, ii) amino acid composition, iii) rate of absorption, and iv) protein/food texture, may have an impact on metabolic aspects related to hunger including the post-prandial use of protein nitrogen, the flux of peptides and amino acids toward bloodstream, and the secretion of hormones and enzymes. [17] The identification of peptides in the gastrointestinal lumen during digestion of milk proteins has been documented in animals, [18][19][20][21][22] and humans, [23][24][25][26][27] . However, data are still scarce and there is a high diversity between these investigations regarding species, ingested products, dairy matrix, gastrointestinal compartments evaluated, and analytical techniques used.…”
Section: Studies On Digestion Of Milk Proteinsmentioning
confidence: 99%
“…Therefore, with the aim to more closely simulate the in vivo human digestive conditions, we applied in this study, the harmonized basic static in vitro protocol developed within the COST action INFOGEST [16]. Despite its obvious limitation (in vitro static model vs in vivo dynamic digestion), the harmonized INFOGEST in vitro digestion protocol is suitable for the study of digestion of protein-rich food due to its similarity with in vivo digestion [17].…”
Section: Introductionmentioning
confidence: 99%